ANALISIS FAKTOR EKSTERNAL DAN FAKTOR INTERNAL ORGANISASI PELAYANAN SOSIAL RELAWAN MUDA RIAU - R Willya Achmad W; Soni Akhmad Nulhaqim; Sri Sulastri (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
Relawan Muda Riau were formed to answer how social service organizations run in accordance with their corridors, so far young Riau volunteers have focused on helping the Riau provincial government overcome social welfare problems, especially in the areas of economic empowerment and assistance programs for schools in remote Riau. In carrying out this program Riau Young Volunteers often have difficulties, especially in managing internal and external factors. External factors consist of four main factors, namely economic, sociological, political/professional and technological factors. Whereas internal factors consist of organizational goals, mission and philosophy, organizational planning, organizational operations, human resources, technological resources and funding sources.